Agency, Adaptation, and Audience: Re-visioning the Legend of Mahsuri in Selected Contemporary Malaysian Young Adult Fiction - Osman, Sharifah Aishah (Department of English, Faculty of Arts and Social Sciences, University of Malaya, 2018)
The legend of Mahsuri is inseparable from the historical and cultural identity of the people of Langkawi, Kedah. Despite its graphic depiction of mob violence and brutality, and perhaps even because of it, the legend transmitted through the folktale, retains its hold on the collective memory of many Malaysians. As the oldest and most widely known form of literature for children, the folktale reflects the concerns of a “monarchistic, patriarchal, and feudal society” and its attendant limitations (Zipes 8). Yet folktales are also among the most subversive texts in children’s literature, and often “support the rights of disadvantaged members of the population – children, women, and the poor – against the establishment” (Lurie 16). In acknowledging the interrogative power of the folktale, especially its ability to challenge the ideological position of the Malay woman as constructed by dominant interests, this essay argues that the legendary story of Mahsuri, as well as its subsequent adaptations, provides important insights into the contemporary relevance of the folktale to the contestation of the patriarchal, feudalistic, and nationalistic discourses circulating in modern, multicultural Malaysia. This essay discusses two contemporary textual representations of the Mahsuri legend – Lee Su Ann’s young adult murder mystery, The Curse (2005), and Preeta Samarasan’s short story of interracial love, “Mahsuri” (2011) – in order to illustrate how each draws attention to the subjugated status of women in contemporary Malay society. As riveting examples of Malaysian young adult fiction, both stories reflect the critical engagement with, and interrogation of, issues of gender, racial, and religious identity in contemporary multicultural Malaysia by foregrounding the struggle for power and possession over the body of the idealized Malay woman and through their mutual emphasis on the repercussions of Mahsuri’s “curse” on their protagonists.